Detailed morphobiometric studies of Bursaphelenchus xylophilus and characterisation of other Bursaphelenchus species (Nematoda: Parasitaphelenchidae) associated with Pinus pinaster in Portugal - Penas, Ana Catarina (2007)
Detailed studies on Bursaphelenchus xylophilus are provided in this contribution. Comparative observations between field and cultured populations of this species demonstrated significant size differences: cultured specimens overall displayed larger size in all morphometric parameters. A principal component analysis (PCA) of the individuals undergoing moulting allowed their separation in four groups namely J2-J3, J3-J4, J4F-F, and J4M-M; gonad length mean values of these four groups made possible to distinguish the non-moulting groups J2, J3, J4F, J4M and adults. Seven Bursaphelenchus species (B. hellenicus, B. leoni, B. pinasteri, B. sexdentati, B. teratospicularis, B. tusciae and B. xylophilus), associated with Pinus pinaster in Portugal, were charaterized, including biometrical measurements and ratios as well excised spicules observed under SEM; furthermore, B. hellenicus, B. pinasteri, B. sexdentati, B. tusciae and B. xylophilus were characterised on the basis of their ITS-RFLP profiles. B. sexdentati and B. xylophilus were the only species found in high numbers in some of the samples.